RECCAS - REmoval of Cytokines during CArdiac Surgery: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Baumann, Andreas; Buchwald, Dirk; Annecke, Thorsten; Hellmich, Martin; Zahn, Peter; Hohn, Andreas
Abstract Background On-pump cardiac surgery triggers a significant postoperative systemic inflammatory response, sometimes resulting in multiple-organ dysfunction associated with poor clinical outcome. Extracorporeal cytokine elimination with a novel haemoadsorption (HA) device (CytoSorb®) promises to attenuate inflammatory response. This study primarily assesses the efficacy of intraoperative HA during cardiopulmonary bypass (CPB) to reduce the proinflammatory cytokine burden during and after on-pump cardiac surgery, and secondarily, we aim to evaluate effects on postoperative organ dysfunction and outcomes in patients at high risk. Methods/design This will be a single-centre randomised, two-arm, patient-blinded trial of intraoperative HA in patients undergoing on-pump cardiac surgery. Subjects will be allocated to receive either CPB with intraoperative HA or standard CPB without HA. The primary outcome is the difference in mean interleukin 6 (IL-6) serum levels between the two study groups on admission to the intensive care unit. A total number of 40 subjects was calculated as necessary to detect a clinically relevant 30 % reduction in postoperative IL-6 levels. Secondary objectives evaluate effects of HA on markers of inflammation up to 48 hours postoperatively, damage to the endothelial glycocalyx and effects on clinical scores and parameters of postoperative organ dysfunction and outcomes. Discussion In this pilot trial we try to assess whether intraoperative HA with CytoSorb® can relevantly reduce postoperative IL-6 levels in patients undergoing on-pump cardiac surgery. Differences in secondary outcome variables between the study groups may give rise to further studies and may lead to a better understanding of the mechanisms of haemoadsorption. Trial registration German Clinical Trials Register numberDRKS00007928 (Date of registration 3 Aug 2015)